Present-day issues of social and economic development of communes based on the Podlaskie voivodeship - Bugowski, Łukasz Karol (Współczesne problemy rozwoju społeczno-gospodarczego gmin na przykładzie województwa podlaskiego, 2020)
Social and economic development is characterised by its spatial diversity. Its conditions on local level usually occur on a larger scale on regional level. Thus, the analysis of development on local level is not only substantively justified but also constitutes an elaboration of particular elements of the regional development. The main goal of this article is to analyse the indicators of local development using the example of the Podlaskie voivodeship considering the division into rural, urban-rural and urban communes. The method consists in a synthetic indicator based on sub-indicators which cover aspects of social and economic development. The main conclusion is that local development will depend less and less on ‘hard’ infrastructure investment and more and more on qualitative aspects, especially as far as urban-rural communes in Podlaskie are concerned
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 5-16